Inter simple sequence repeat (ISSR) as genetic marker system in molecular systematics and phylogenetics - Rahman, M Oliur (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 103-118, 2004 (June)